Application of Computer-Assisted Audit Tools and Techniques (CAATTs) in audit firms - Ghani, Rusman; Rosli, Khairina; Ismail, Noor Azizi; Saidin, Siti Zabedah (Akademia Baru, 2017)
This paper explores the application of Computer-Assisted Audit Tool and Techniques (CAATTs) and the reasons for the use of CAATTs application among audit firms in Malaysia. The study uses survey and interview methods to explore the types of CAATTs applied by the respondent firms. The results demonstrate that the application of CAATTs among audit firms varies by firm size. The application of advanced CAATTs, i.e. Embedded Audit Modules, Parallel Simulation Software, Test Data were the highest in Big-4 firms, as compared to medium and small sized firms. The reasons that influence them to practice the use of CAATTs are availability of financial resources, partners’ expertise and their clients’ nature of operation. The application of CAATTs is not compulsory by the law or standards. However, there is an encouragement from the authorities and accounting bodies for the practitioners to apply CAATTs in their audit works. The findings contribute in providing inputs to the policy makers and practitioners on how to enhance the application of CAATTs into the current practice of auditing process and future regulations. The present study also opens up opportunities and provides avenues for more indepth research on the subject of CAATTs.